Dynamic Modeling of a MEMS Electro-Thermal Actuator Considering Micro-Scale Heat Transfer With End Effectors - Zhu, Hengbo; Cao, Yun; Ma, Wanli; Kong, Xiaoyu; Lei, Shenghong; Lu, Haining; Nie, Weirong; Xi, Zhanwen (Journal of microelectromechanical systems, 2024)
Dynamic modeling is the basis for predicting the behavior of the electro-thermal actuator (ETA). Although the sequential decoupling method, often used in previous studies, has been able to model the dynamics of ETAs, most of them focused only on the ETAs themselves, and few considered the effects of end effectors. In this work, a dynamic multi-fields coupling model considering the effects of end effectors was developed. Due to the end effector, the dynamic model changes from a one-way coupled problem to a complex two-way coupled problem, limiting the commonly used sequential decoupling method. In order to solve the two-way coupled problem, a thermal microscope system was first employed to study the heat transfer characteristics between the ETA and the end effector at different thicknesses of the air gap. Subsequently, a combination of the Crank-Nicolson finite difference method and finite element method was employed to solve the problem numerically. It was eventually demonstrated by experiments that the presented dynamic model is an effective analytical technique to predict the dynamic behavior of the ETA with end effectors.